The association of HLA-C alleles with multiple myeloma in Chinese patients - Xiaojing Wang; Gang An; Jiying Wang; Yan Zhang; Qinghua Li; Hui wei; Lugui Qiu; Kun Ru (Experimental Hematology & Oncology, 2018)
Abstract Background The positive association of multiple myeloma (MM) risk with HLA-C loci C*07:02 g and C*02:02 g, and the negative association of that with C*05:01 g were statistically significant in Whites have recently been reported. However, no association between HLA-C alleles and MM risk was found in Asians/Pacific Islanders. Here we identified 316 Chinese patients with MM, and reported the results of our investigation of HLA-C in MM in Chinese population. Methods We identified 316 Chinese patients with MM diagnosed in our hospital, and typed for HLA-C by using Sanger sequence-based typing. The control was from laboratories of China Marrow Donor Program (CMDP), where HLA high resolution was provided in 564,856 volunteer adult donors. Results In contrast to the association of MM risk in Whites, we did not find the similar association in Chinese population. Nevertheless, four new associations between the MM risk were identified in Chinese patients. Our data demonstrated that Chinese patients with MM carry significantly increased frequencies of HLA-C*03:03 (FDR = 0.0269), HLA-C*07:63 (FDR = 0.0278) and HLA-C*08:22 (FDR = 0.0442) comparing with controls, while significantly decreased frequency of HLA-C*01:02 (FDR = 0.0414) comparing with controls. Conclusion Therefore, HLA-C region is a key risk locus for MM in Chinese population.